New opportunities for overweight* and obesity pharmacotherapy - Bogdański, Paweł (Lekarz POZ, 2017)
Results of epidemiological studies show a permanent increase in overweight and obesity prevalence. It was demonstrated beyond reasonable doubt that overweight leads to many adverse health consequences. Realistic goals and timeframe estimation are crucial for obesity treatment. Patients should also be motivated in a proper way. A comprehensive program for weight reduction should be based on diet modification, increase in physical activity and behavioral therapy. In some patients pharmacotherapy can be considered. A new medicinal product available on the market since November 2016 under the trade name Mysimba provides wider possibilities of pharmacological treatment and increases chances for efficacious management of overweight* and obesity.